2023
DOI: 10.1039/d3cc00422h
|View full text |Cite
|
Sign up to set email alerts
|

An umpolung strategy for chemically selective intermolecular cross-enolate-type coupling of N-alkenoxypyridinium salts with aldehydes

Abstract: An efficient method for the synthesis of 1,4-ketoaldehydes via cross-coupling of N-alkenoxyheteroarenium salts and primary aldehydes is developed. This method works with broad substrate scope and excellent functional group compatibility....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…11 These N -alkenoxypyridinium salts display novel enolate umpolung reactivities and could serve as a surrogate of highly reactive acylcarbenium ions to react with various nucleophiles. 12 In 2019, Xu and coworkers realized the synthesis of N -alkenoxypyridinium salts using an Ag( i )-catalyzed procedure. 13 Ye and coworkers developed a series of Zn(OTf) 2 -catalyzed alkyne oxidation reactions of ynamides using N -oxides, and the reactions were supposed to proceed through a Lewis acid-catalyzed S N 2′ pathway on N -alkenoxypyridinium intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…11 These N -alkenoxypyridinium salts display novel enolate umpolung reactivities and could serve as a surrogate of highly reactive acylcarbenium ions to react with various nucleophiles. 12 In 2019, Xu and coworkers realized the synthesis of N -alkenoxypyridinium salts using an Ag( i )-catalyzed procedure. 13 Ye and coworkers developed a series of Zn(OTf) 2 -catalyzed alkyne oxidation reactions of ynamides using N -oxides, and the reactions were supposed to proceed through a Lewis acid-catalyzed S N 2′ pathway on N -alkenoxypyridinium intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…21 We previously reported that N-alkenoxyheteroarenium salts derived from alkynes could behave as synthetic equivalents to highly reactive acylcarbenium cations. 22,23 We postulate that the reaction between these two organic salts initiates with rapid ion exchange, followed by an intramolecular addition reaction, ultimately yielding α-haloketones (Figure 1C). However, it should be noted that this reaction faces the challenge of multiple reactive sites on the N-alkenoxyheteroarenium salt, where halide anions may also undergo addition to the pyridine ring.…”
Section: ■ Introductionmentioning
confidence: 99%